Research frontiers in penaeid shrimp reproduction: future trends to improve commercial production - Alfaro-Montoya, Jorge (2019)
Shrimp farming worldwide is based on a similar technological package, characterized by three phases: Controlled Reproduction, Larvae Culture, and Grow-out Culture. This basic aquaculture package uses broodstock animals, with different levels of fundamental genetic selection, induced to mature and reproduce based on unilateral eyestalk ablation. This review identified ten reproduction-related research subjects that can improve the shrimp industry based on basic scientific knowledge and four levels of application: eyestalk ablation alternatives, larvae production, product protection, and grow-out yield improvement. Species-specificity must be considered in developing biotechnology solutions. Alternatives to eyestalk ablation for controlling ovarian maturation are based on neurotransmitter regulation in Litopenaeus; however, the environmental impact of this approach has to be evaluated. Maturation by RNAi requires further evaluation, and maturation pheromones have not been explored. Sex reversal, hybridization, in vitro fertilization, and seedstock cryopreservation of penaeids require fundamental research. Triploid culture and genetic selection can be applied to some species for product protection; however, for L. vannamei, triploidization is not practical yet.